Increasing Public Interest through School Image Branding through a Trending Approach - Ahmad Walid; Abd. Malik (Educazione: Journal of Education and Learning, 2023)
This study aims to examine the branding strategy applied by MA Nurul Jadid in increasing the interest of the public, especially parents of prospective students, in choosing a school. In the context of increasingly competitive education, it is essential for educational institutions, especially madrasas, to have a strong image that reflects the quality and values they carry. This study uses a qualitative approach with a case study method, involving in-depth interviews with school managers, teachers, and student parents to collect data on public perception of school branding. The study's findings show that an effective branding strategy at MA Nurul Jadid involves implementing a standardized managerial system, developing superior programs based on religion, and using social media as the primary communication channel. In addition, the Tahfidz Qur'an program and the school's slogan reflect a strong vision and mission and significantly strengthen the school's image. The results of this study provide new insights into how madrassas can build positive branding by integrating religious values into their strategies. These findings also provide important implications for madrasah managers and other religious education institutions to design a more integrated branding strategy focusing on education quality and values relevant to the community.